DEVELOPMENT OF A WEB-BASED REGISTRATION SYSTEM AT THE TUNJUNGSEKAR SUBDISTRICT OFFICE - Deddy Rudhistiar; Muhammad Hasan Wahyudi; Cornelia Luba Tara Boro; Siti Mutiara; Thesa Adi Saputra Yusri (Computer Science Department, Malang National Institute of Technology, 2025)
The Tunjungsekar subdistrict office regularly organizes various activities involving local participants. Currently, the registration process is conducted using Google Forms, which, while facilitating data collection, presents challenges such as duplicate registrations and difficulties in managing participant quotas. Additionally, participant data processing and activity summaries are still handled manually, reducing administrative efficiency. To address these issues, a web-based registration system was developed using PHP with the Laravel framework and a MySQL database. This system enables automatic validation to prevent duplicate registrations and allows for more effective participant quota management. Blackbox taesting shows that the system works, the system functions properly without significant bugs or errors. With this system, activity data management becomes more structured, participant records are more accurate, and administrative processes are more efficient. The implementation of this system is expected to support the digitalization of community services and enhance the community’s experience in accessing information and services more practically and systematically